RNAseq and targeted metabolomics implicate RIC8 in regulation of energy homeostasis, amino acid compartmentation, and asexual development in Neurospora crassa - Monique Quinn; Alexander J. Carrillo; Lida Halilovic; Katherine A. Borkovich (mBio)
ABSTRACT Heterotrimeric G protein signaling pathways control growth and development in eukaryotes. In the multicellular fungus Neurospora crassa, the guanine nucleotide exchange factor RIC8 regulates heterotrimeric Gα subunits. In this study, we used RNAseq and liquid chromatography-mass spectrometry (LC-MS) to profile the transcriptomes and metabolomes of N. crassa wild type, the Gα subunit mutants Δgna-1 and Δgna-3, and Δric8 strains. These strains exhibit defects in growth and asexual development (conidiation), with wild-type and Δgna-1 mutants producing hyphae in submerged cultures, while Δgna-3 and Δric8 mutants develop conidiophores, particularly in the Δric8 mutant. RNAseq analysis showed that the Δgna-1 mutant possesses 159 mis-regulated genes, while Δgna-3 and Δric8 strains have more than 1,000 each. Many of the mis-regulated genes are involved in energy homeostasis, conidiation, or metabolism. LC-MS revealed changes in levels of primary metabolites in the mutants, with several arginine metabolic intermediates impacted in Δric8 strains. The differences in metabolite levels could not be fully explained by the expression or activity of pathway enzymes. However, transcript levels for two predicted vacuolar arginine transporters were affected in Δric8 mutants. Analysis of arginine and ornithine levels in transporter mutants yielded support for altered compartmentation of arginine and ornithine between the cytosol and vacuole in Δric8 strains. Furthermore, we validated previous reports that arginine and ornithine levels are low in wild-type conidia. Our results suggest that RIC8 regulates asexual sporulation in N. crassa at least in part through altered expression of vacuolar transporter genes and the resultant mis-compartmentation of arginine and ornithine.IMPORTANCEResistance to inhibitors of cholinesterase-8 (RIC8) is an important regulator of heterotrimeric Gα proteins in eukaryotes. In the filamentous fungus Neurospora crassa, mutants lacking ric8 undergo inappropriate asexual development (macroconidiation) during submerged growth. Our work identifies a role for RIC8 in regulating expression of transporter genes that retain arginine and ornithine in the vacuole (equivalent of the animal lysosome) and relates this function to the developmental defect. Arginine is a critical cellular metabolite, both as an amino acid for protein synthesis and as a precursor for an array of compounds, including proline, ornithine, citrulline, polyamines, creatine phosphate, and nitric oxide. These results have broad relevance to human physiology and disease, as arginine modulates immune, vascular, hormonal, and other functions in humans.